Ngudari reribed: internalization of Ki Ageng Suryomentaram's values to increase mindfulness - Finayanti, Juwita; Anggriana, Tyas Martika (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
Of happiness can arise from mindfulness because mindfulness creates clarity of consciousness, awareness that does not conceptualize and discriminate, awareness and flexible attention, can have an empirical stand against reality, consciously orientates towards the present, awareness and awareness that stable and sustainable. The purpose of this study was to examine the values contained in the teachings of Ki Ageng Suryomentaram to be applied as a counselling technique based on Indonesian culture. This research method uses a qualitative approach with the type of Gadamerian hermeneutics. The results of the research findings show that: (1) Mindfulness in this context helps to make individuals aware that happiness is not only about fulfilled desires but accepting themselves as they are and fostering an appreciation for moments that occur in life. (2) The compatibility between the technique of "ngudari reribed" and mindfulness lies in the goal of achieving a happy life. (3) Identification of the values contained in Ki Ageng Suryomentaram's discourse can be applied in the "ngudari reribed" counselling technique to increase mindfulness. Mindfulness will help a person feel at peace without worrying about the future and meditating on the past.